Emerging Vector-Borne Nipah Virus Infection: Unexplored Hazards, Diagnostic Challenges, and the Potential of Phytomedicine-Based Therapeutics - Adhikary, Krishnendu; Barman, Saurav; Chowdhury, Sumana Roy; Ganguly, Krishnendu; Mohanty, Satyajit; Gupta, Muskan; Mukherjee, Tuhin; Dhua, Rumpa; Banerjee, Pradipta; Maiti, Rajkumar (Current Pharmaceutical Design, 2025)
<span class=
Keywords: phytochemical